Linking the energy transition and economic development: A framework for analysis of energy transitions in the global South. (August 2022) - Swilling, Mark; Nygaard, Ivan; Kruger, Wikus; Wlokas, Holle; Jhetam, Tasneem; Davies, Megan; Jacob, Merin; Morris, Mike; Robbins, Glen; Funder, Mikkel; Hansen, Ulrich Elmer; Olsen, Karen Holm; et al.
Abstract: We are observing a significant increase in the deployment of large scale solar and wind technologies in the global south, and it is therefore a strategically and academically important focus of inquiry to understand context-specific spaces for locally-embedded actors to initiate energy transitions. This paper examines the linkages between the energy transition and economic development, and has attempted to do this by developing an approach that brought into focus the institutional micro-economics of four key dimensions of the economic development process, namely (a) the impact of the auction mechanism; (b) the key role MNCs play in the global value chain; (c) how developmentally-oriented states have attempted to harness the resulting investment flows by using LCRs; and (d) the local-level development impacts of utility-scale renewable energy power plants on local communities. Drawing from the South African energy transition as a case we argue that the complex interaction between highly globalized value chain actors, path dependent local institutions and interests of incumbent local actors sheds new light on the dynamics of rapid institutional change during energy transitions in a global South context. We use the South African case to develop a framework for analysing the energy transition in the global south that brings into relief the complex dynamics of change, learning and experimentation. Our focus is on the way rule-setting and the actions of actors within institutions (dis-)enables financial flows, institutional change and socio-technical adaptation in a fast-changing environment driven by responses to climate change and the challenge of rapid decarbonisation.